(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the study of the problems of legal qualification of illegal blood trade. Blood and its components are anatomical materials and can be recognized as the subject of the crime provided for in Part 4 of Art. 143 of the Criminal Code of Ukraine. The subject of this crime is general. Trafficking in blood by a non-specialist subject is a criminal offense. In the case of a violation of the procedure established by law for the sale of blood by a special subject - an official of a subject of the blood system or a health care institution, such actions are subject to qualification under Art. 45-1 of the Code of Administrative Offenses. Illegal blood trade is a socially dangerous act, it creates risks for public health (due to the uncontrolled circulation of this anatomical material and the impossibility of taking sufficient measures to prevent the transmission of infectious diseases). Countering these actions is in line with Ukraine’s international obligations.